DETERMINANTS OF MOBILE PAYMENT USAGE AND THE MODERATING EFFECT OF GENDER: EXTENDING THE UTAUT MODEL WITH PRIVACY RISK - Lee, Jin-Myong (International Journal of Electronic Commerce Studies, 2019)
Mobile payment is an emerging and important application for e-commerce and traditional offline commerce. This study investigates the determinants of the intention to use mobile payment services (MPS) and the extent to which these relationships are moderated by gender. For this purpose, a conceptual model is proposed by extending the UTAUT model with perceived risk. Data are from a web-based survey conducted using South Korean consumers (n = 528). Structural equation results reveal that performance expectancy and social influence have a positive effect on the intention to use MPS, whereas privacy risk has a negative effect. Gender was found to moderate two paths in the model, such that a high level of facilitating conditions increased the intention to use MPS for males but not for females, whereas privacy risk decreased the intention to use MPS for females but not for males. Theoretical and managerial implications for researchers and marketing practitioners are also discussed.